NEW TRENDS IN THE DEVELOPMENT OF EDUCATION IN UKRAINE - Силадій, Іван (Професіоналізм педагога: теоретичні й методичні аспекти, 2020)
Modernization of national education causes new challenges in the system of human preparation for life. At the same time, these challenges are due to the processes of Ukrainian state formation - the establishment of market and democratic relations, the formation of civil society and political nation, the revival of national culture and more. Equally, the challenges in the education system are caused by the crisis in the economy, rising unemployment, falling living standards, rising crime and more. In addition, only after acquiring national outlines, Ukrainian education is on its way to entering the multinational European space. The solution of the related problems requires the development of deep and extensive scientific and pedagogical research of modernization educational challenges. Globalization and informatization, as well as Ukraine’s entry into the European educational space, are at the same time a threat and an opportunity to improve the national education system. The main task is to prevent threats and create favorable conditions for positive impact. In response to the challenges of globalization, the development of a national idea of education is proposed, the content of which is to preserve and increase national educational traditions. Ukraine's accession to the European educational space is based on the tasks of the Bologna Declaration, the essence of which is to introduce a pan-European model of education in the domestic cultural and educational space, which should be based on common fundamental principles of its functioning. The analysis leads to the conclusion that the modernization of the education system in Ukraine in the context of modern globalization processes is aimed at the development of basic science, Ukrainian and world cultural values, focus on the ideals of democracy and humanism necessary for the existence and development of civil society.